Penyuluhan Gemar Bersedekah Di Lingkungan TK ABA 37 Kota Malang - Rahmi Amalia (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2022)
Purpose of the study: To help students of kindergarten ABA 37 to better understand the benefits of almsgiving and make alms a preffered practice Methodology: In this study, the methods used are mentoring which includes socialization, counseling, practice, monitoring, and evaluation. Main Findings: During the service process, it was found that kindergarten ABA 37 students have not fully practiced the value of giving alms in everyday life and still need to be motivated to do so. Applications of this study: This devotion is useful for students of TK ABA 37 which is useful to instill the love of almsgiving early on. Novelty/Originality of this study: In this service, we have been able to identify the problems experienced by students by using socialization, counseling, practice, monitoring, and evaluation, the extension of almsgiving will be able to increase awareness of kindergarten ABA 37 students to be diligent in almsgiving.